Strategi Peningkatan Pengelolaan Kawasan yang Efektif dan Berkelanjutan pada Desa Wisata Kandri Kota Semarang - Riza Irwianto Tirana; Febrina Nur Rahmi Briliana (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Tourism is currently being developed in Indonesia. One of the tourism developments is in Kandri Tourism Village. Kandri Tourism Village is located in Gunungpati District, Semarang City. Its management currently utilizes natural and cultural attractions developing in the community. Its management efforts face various problems that challenge the stakeholders involved. Problems that arise in the management of Kandri Tourism Village are related to the provision of supporting tourism facilities and infrastructure, promotional activities, and participation from the community and stakeholders directly involved. Therefore, a direction or strategy is needed so that it can be used for the management of Kandri Tourism Village. The purpose of this research is to formulate the right management strategy to improve the quality of tourism. The types and sources used are secondary data related to managing tourist villages. The methods used are stakeholder role mapping analysis, linear responsibility analysis using the RACI Matrix, SWOT analysis, and IFAS and EFAS analysis. The results of this study are in the form of an appropriate strategy for Kandri Tourism Village using a W-O strategy, including adding supporting tourism facilities and infrastructure so that they can meet the standards in the tourism provision regulations, conducting training activities to improve management human resources so that they can open management cooperation with other parties and increase promotional activities that utilize technological developments.